FROM LIABILITY TO SUSTAINABILITY: HOW COST OF DEBT AND AUDIT COMMITTEE CHARACTERISTICS DRIVE GREEN INNOVATION? - Sheren Mey Line Br Manik; Valentine Siagian; Riky Sai Maruli (Universitas Tidar, 2024)
This study aims to investigate the impact of the cost of debt and audit committee characteristics on green innovation. The successful implementation of green innovation in the modern era has become essential for improving the overall quality of the sustainable environment. This study focuses on a sample of industrial sector entities listed on the Indonesia Stock Exchange that issued sustainability reports during the 2021–2022 period. Logistic regression analysis is employed as the primary analytical method. The findings reveal that the cost of debt and the characteristics of the audit committee do not significantly influence green innovation. This outcome may be explained by the limited data availability regarding the extent of research and development disclosures provided by industrial firms. The study aims to contribute meaningful insights to encourage listed industrial companies on the Indonesia Stock Exchange to enhance the comprehensiveness of their sustainability-related innovation disclosures.